Diagnostic Rates Differ on the Basis of the Number of Read Days with the Use of the InPouch Culture System for Trichomonas vaginalis Screening - Rivers, Charles. A. (American Society for Microbiology, 2013)
The InPouch Trichomonas vaginalis test is the gold standard for clinical culture for Trichomonas vaginalis screening. The current package insert recommends an examination period of 3 days. After review of 2,499 InPouch tests spanning 13 years, we observed that examination up to 3 days will detect only 82.8% (95% confidence interval [CI], 79.0% to 86.2%) of positive specimens.